УПРАВЛЕНИЕ МАГНИТОЭЛЕКТРИЧЕСКИМ ГЕНЕРАТОРОМ С АКСИАЛЬНЫМ ПОТОКОМ - Чумак, В.В.; Монахов, Е.А. (Інститут електродинаміки НАН України, Київ, 2016)
Article deals with an special proposed axial flux permanent magnet generator designed for a control of magnetic flux and consequently external characteristic of generator, Proposed design was investigated by three - dimensional field mathematical model in modern programs. Axial flux permanent magnet machine was manufactured and tested after results of research. Experimental results proved the results of modeling. Also an electric scheme for control of output voltage based on Arduino Uno was designed and investigated. The scheme implements pulse - width modulation of control voltage. References 6, figures 5.